Multilingualism and fluent switching between languages - Вракіна, Вікторія Вікторівна; Танько, Євгенія Владиславівна; Беркутова, Тетяна Іванівна (CPN Publishing Group, 2024)
The prevalence and cognitive mechanisms of multilingualism are explored, emphasizing the cognitive advantages and cultural competence associated with bilingualism and multilingualism. The role of stereotypes and associations in language switching is discussed, highlighting how sociocultural factors influence language choice. Techniques for achieving language proficiency and switching between languages are also provided, emphasizing the combination of art and science necessary for rapid adaptation to diverse linguistic environments.
Keywords: multilingualism; bilingualism; switching between languages; stereotypes; special techniques